2021
DOI: 10.2147/jmdh.s313209
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Lung Function in Patients with Cystic Fibrosis in Western Romania

Abstract: Purpose The aim of this cross-sectional study was to identify the major factors influencing pulmonary function in CF patients from western side of Romania. Patients and Methods The study enrolled 51 patients with CF between the ages of 6 and 27.8 years who were monitored at regular visits to the National Cystic Fibrosis Centre and Pius Branzeu County Hospital in Timisoara, Romania, over a period of 2 years. The relationships between lung function, as measured by forced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…In our study, a lower BMI was associated with a higher LCI (p = 0.001); poor nutritional status was associated with worse lung function and a decreased vitamin D level, as stated in previously published journals [2,44].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, a lower BMI was associated with a higher LCI (p = 0.001); poor nutritional status was associated with worse lung function and a decreased vitamin D level, as stated in previously published journals [2,44].…”
Section: Discussionsupporting
confidence: 87%
“…This study reports that, in the presence of CFLD, lung function is more deteriorated, as expressed by a higher LCI value (p = 0.000). A previous study [2] has proved that the presence of co-morbidities such as CFLD and CFRD is unrelated to lung function, as expressed by spirometry. Although a recent study about abnormal glucose tolerance and lung function in cystic fibrosis patients had concluded that patients with abnormal glucose tolerance or even with CFRD [37] have worse lung function [38], these findings were not supported by our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cystic fibrosis (CF) is the most common potentially fatal monogenic disease in the Caucasian population, with autosomal recessive transmission and a remarkable clinical polymorphism [ 1 ]. Typical CF manifestations include obstructive lung disease and chronic diarrhea, with several complications such as liver and bone disease, CF-related diabetes, which can occur in time [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study‘s outcome revealed that FOT is a consistent alternative technique for lung function measuring in the study population, being able to assess expiratory flow limitation as well as lung compliance changes. The importance of the study resides in functional evaluation of bone- and lung-affecting chronic disease, especially significant as lung disease is the most important outcome predictor for this pathology ( 5 ), and it is imperative to envisage the changes in lung structure and function ( 6 ).…”
mentioning
confidence: 99%